Once again: Gregory of Nyssa on universals - Zachhuber, J (Oxford University Press (OUP), 2005)
This essay takes up the contentious issue of Gregory of Nyssa's use of a theory of the universal. It is argued that Gregory, in his trinitarian theology and elsewhere in his thought, employs with remarkable coherence a kind of theory for which the universal is essentially the whole of its individuals (collection theory). For Gregory this is a realistic theory in which the concept of the whole is either entirely detached from that of the individuals (as ousia or hupostasis in his trinitarian theory) or related to them as actual to potential nature (for example in his cosmology). It is characteristic for him that he makes the whole collection the object of reference for the substance-sortal. This theory helps him avoid (to some extent) doctrinal ramifications within trinitarian theology as it explains the Trinity as a perfect unity-in-trinity which is both irreducibly one and irreducibly three.